Host plant‐related variation in thermal tolerance of Eldana saccharina. Issue 2 (29th December 2013) - Kleynhans, Elsje; Conlong, Des E.; Terblanche, John S.
Abstract Understanding tolerance of thermal extremes by pest insects is essential for developing integrated management strategies, as tolerance traits can provide insights into constraints on activity and survival. A major question in thermal biology is whether thermal limits vary systematically with microclimate variation, or whether other biotic or abiotic factors can influence these limits in a predictable manner. Here, we report the results of experiments determining thermal limits to activity and survival at extreme temperatures in the stalk borer Eldana saccharina Walker (Lepidoptera: Pyralidae), collected from either Saccharum spp. hybrids (sugarcane) (Poaceae) or Cyperus papyrus L. (Cyperaceae) and then reared under standard conditions in the laboratory for 1–2 generations. Chill‐coma temperature (CTmin), critical thermal maximum (CTmax), lower lethal temperatures (LLT), and freezing temperature between E. saccharina collected from the two host plants were compared. CTmin and CTmax of E. saccharina moths collected from sugarcane were significantly lower than those from C. papyrus (CTmin = 2.8 ± 0.4 vs. 3.9 ± 0.4 °C; CTmax = 44.6 ± 0.1 vs. 44.9 ± 0.2 °C). By contrast, LLT of moths and freezing temperatures of pupae did not vary with host plant [LLT for 50% (LT50) of the moth population, when collected from sugarcane: −3.2 ± 0.5 °C, from C. papyrus: −3.9 ± 0.8 °C]. Freezing temperatures of pupae collected from C. papyrus were −18.0 ± 1.0 °C and of those from sugarcane −17.5 ± 1.8 °C. The E. saccharina which experienced the lowest minimum temperature (in C. papyrus) did not have the lowest CTmin, although the highest estimate of CTmax was found in E. saccharina collected from C. papyrus and this was also the microsite which reported the highest maximum temperatures. These results therefore suggest that host plant may strongly mediate lower critical thermal limits, but not necessarily LLT or freezing temperatures. These results have significant implications for ongoing pest management and thermal biology of these and other insects.